Pengaruh Contextual Supports and Barriers terhadap Career Decision Making Self-Efficacy pada Siswa SMK Negeri di Kota Bandung - Raisa Rizka Dwi Rahmawati; Temi Damayanti Djamhoer (UNISBA Press, 2022)
Abstract. Vocational High School students are not only required to equip themselves with knowledge and skills related to their expertise. Still, they are also needed to add information related to jobs and careers currently available and prepare their career options and plans. Therefore, in addition to increasing knowledge and practical skills, vocational students also need to increase confidence in making career decisions. The higher the faith, the students can face the tasks of making career decisions well. Contextual factors play an essential role in determining how much confidence an individual has in his ability to meet the functions of making career decisions. The purpose of this study was to assess the effect of Contextual Supports and Barriers on Career Decision-Making Self-Efficacy in State Vocational High School students in Bandung City. This study consisted of 260 grade 12 students from 8 State Vocational Schools in Bandung City. Career Decision-Making Self-Efficacy is measured using the Career Decision Making Self-Efficacy Short Form (CDSE-SF) adapted by Sawitri et al. (2012). Contextual Support and Barrier data collection were carried out using the Contextual Support and Barrier instrument developed by Lent et al. (2001). The results of this study indicate the effect of contextual support of 34.85% and contextual barrier of 0.53% on career decision-making self-efficacy in State Vocational High School students in Bandung City. Abstrak. Vocational High School students are not only required to equip themselves with knowledge and skills related to their expertise. Still, they are also needed to add information related to jobs and careers currently available and prepare their career options and plans. Therefore, in addition to increasing knowledge and practical skills, vocational students also need to increase confidence in making career decisions. The higher the faith, the students can face the tasks of making career decisions well. Contextual factors play an essential role in determining how much confidence an individual has in his ability to meet the functions of making career decisions. The purpose of this study was to assess the effect of Contextual Supports and Barriers on Career Decision-Making Self-Efficacy in State Vocational High School students in Bandung City. This study consisted of 260 grade 12 students from 8 State Vocational Schools in Bandung City. Career Decision-Making Self-Efficacy is measured using the Career Decision Making Self-Efficacy Short Form (CDSE-SF) adapted by Sawitri et al. (2012). Contextual Support and Barrier data collection were carried out using the Contextual Support and Barrier instrument developed by Lent et al. (2001). The results of this study indicate the effect of contextual support of 34.85% and contextual barrier of 0.53% on career decision-making self-efficacy in State Vocational High School students in Bandung City.